Hederagenin promotes SIRT6 to attenuate epidural scar formation by aggravating PRMT1 deacetylation - Xiao-Chen Fan; Jue Wang (Bone & Joint Research)
Aims: The formation of a postoperative epidural scar induced by epidural fibrosis is the main reason for recurrence of lumbar disc herniation after laminectomy. Hederagenin (HE) has been found to be widely present in various medicinal plants and has various pharmacological functions. This study aimed to investigate the effect and regulatory mechanism of HE on epidural scar formation. Methods: Transforming growth factor beta 1 (TGF-β1)-stimulated epidural scar fibroblasts were used as an in vitro cell model. Based on that, HE treatment was carried out along with sirtuin-6 (SIRT6) silence or protein arginine N-methyltransferase 1 (PRMT1) overexpression. The interaction between SIRT6 and PRMT1 was evaluated by pulldown and co-immunoprecipitation (CoIP) assays. Then, cell proliferation, apoptosis, and fibrosis were measured by Cell Counting Kit (CCK)-8, flow cytometry, and western blotting. Moreover, the effects of receptor activator of nuclear factor-κB ligand (RANKL) supplementation and endoplasmic reticulum (ER) stress were also evaluated by supplementing recombinant protein and specific inhibitor or activator. Results: HE depressed cell proliferation and fibrosis, while inducing apoptosis of epidural fibroblasts. Meanwhile, HE promoted SIRT6 expression which suppressed PRMT1 acetylation and protein stability. Additionally, HE induced ER stress and upregulated RANKL in epidural fibroblasts via mediating SIRT6/PRMT1 axis. Conclusion: Generally, the therapeutic role of HE treatment on epidural scar formation was exerted by regulating SIRT6/PRMT1 axis-mediated ER stress and RANKL pathway. This study provides evidence of a novel therapeutic measure for epidural scar formation. Cite this article: Bone Joint Res 2025;14(6):516–526.